Elevated activity levels of activating autoantibodies to the GnRH receptor in patients with polycystic ovary syndrome - Elizabeth A. Weedin, D.O., M.S; Heather R. Burks, M.D; Xichun Yu, M.D; Hong Liang Li, M.D., Ph.D; Christopher E. Aston, Ph.D; David C. Kem, M.D; LaTasha B. Craig, M.D (Elsevier, 2020)
Objectives: 1) To confirm the correlation of GnRH receptor (GnRHR) activating autoantibody (AAb) activity with polycystic ovary syndrome (PCOS) diagnosis in large well defined cohorts; and 2) to evaluate suppression of AAb activity with GnRH antagonist medication in transfected GnRHR cells exposed to serum of PCOS patients. Design: Cross-sectional matched case-control study. Setting: University-based research facility. Patient(s): Sera from 200 patients with PCOS from the Pregnancy in Polycystic Ovary Syndrome II (PPCOS II) trial and from 200 race, parity-, age-, and body mass index (BMI)-matched ovulatory unexplained infertile control patients from the Assessment of Multiple Intrauterine Gestations from Ovarian Stimulation (AMIGOS) trial were obtained and used for this study. Intervention(s): GnRHR AAb activity was determined with the use of the GeneBlazer cell-based fluorescence resonance energy transfer assay with and without cetrorelix, a GnRH antagonist. Main Outcome Measure(s): 1) GnRHR AAb activity in PCOS patients compared with control subjects; and 2) effectiveness of GnRH antagonist in suppressing GnRHR AAb activity. Result(s): GnRHR AAb activity levels in the PCOS group were significantly higher than in the control group. With cetrorelix, GnRHR AAb activity was largely suppressed in the PCOS group but not in the control group. These differences remained significant after adjusting for within-pair differences in age, BMI, and antimüllerian hormone (AMH) levels. Conclusion(s): We confirmed higher GnRHR AAb activity levels in the sera of a large cohort of PCOS patients compared with unexplained infertile control subjects. Addition of cetrorelix resulted in significant suppression of AAb activity levels in PCOS patients as a group whereas control subjects were unaffected. GnRHR AAb, along with patient age and AMH level, may provide a promising future diagnostic test for PCOS.